Influence of multidrug resistant organisms on the outcome of diabetic foot infection - Saltoglu, Nese; Ergonul, Onder; TULEK, Necla; Yemisen, Mucahit; KADANALI, Ayten; KARAGOZ, Gul; BATIREL, Ayse; AK, Oznur; SONMEZER, Cagla; Eraksoy, Haluk; Cagatay, Atahan; Surme, Serkan; et al. (My University, 2018)
Objectives: We described the clinical outcomes of the diabetic patients who had foot infections with multidrug resistant organisms.